Charpy and Izod Method Impak Strength Analysis on ST 37 Steel with Temperature Variations - Boangmanalu, Eka Putra Dairi; Pratama, Angga Bahri; Qadry, Al; Saragi, Jandri Fan HT; Sinaga, Franklin Taruyun Hudeardo (Formosa Journal of Science and Technology, 2023)
This research is impact testing using the Charpy and Izod methods, temperature variations of 1500 C, 2500 C and raw material as the research variable. The results of the Charpy test with a variation of 150 0C obtained a maximum absorbed energy of 97.65 J, with an impact value of 0.222 J/mm2. Then the maximum energy absorbed through testing at a temperature of 2500C is 78.28 Joules and the impact value is 0.177 J/mm2. Furthermore, the raw material test results showed that the maximum energy absorbed was 145.96 J with an impact value of 0.330 J/mm2. Izod testing with a temperature of 1500C obtained a maximum absorbed energy of 60.94 J with an impact value of 0.101 J/mm2. Furthermore, the maximum energy absorbed at a temperature of 2500C is 36.83 Joules and the impact value is 0.061 J/mm2. The raw material test results show that the maximum energy that can be absorbed is 80.53 J with an impact price of 0.133 J/mm2